ANALYSIS OF THE EFFECT OF FIRM SIZE, FINANCIAL LEVERAGE, PROFITABILITY, DIVERSIFICATION ON MARKET RISK AND STOCK RETURN (Case Study of Manufacturing Companies in the Consumer Goods Industry Sector Listed on the Indonesia Stock Exchange in 2007-2016) - Agustin, Maulina; Dzulkirom AR, Moch; Darmawan, Ari (Accounting Department,, 2019)
The purpose of this study is to analyze the effect of firm size, financial leverage, profitability, diversification of market risk and stock returns. This research uses quantitative research methods. The population in this study is the consumption sector of manufacturing companies that are listed on the Indonesia Stock Exchange (IDX) during the observation period from 2007-2016. The sample technique using non probability sampling technique with purposive sampling method. The analysis technique used Partial Least Square (PLS). The results showed that the size of the firm had a negative and insignificant effect, while financial leverage, profitability, and diversification had a positive and not significant effect on stock returns and firm size had a negative and significant influence, financial leverage and profitability had a positive and significant relationship, diversification has a positive and not significant effect on market risk and market risk has a positive and significant effect on stock returns.